Method for manufacturing laminate
Patent Information
- Application Number
- JP2023141003
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2043-08-31
AI Technical Summary
【0020】 本発明により、印刷層の画質及び印刷層の脱離性に優れ、脱離した成分の再付着が抑制された、プラスチックリサイクルに適した積層体の製造方法を提供することができる。さらに、回収したプラスチック基材を溶融混練して得られる成形用材料の製造方法、及び、成形用材料を加熱成形して得られる高品位な成型体の製造方法を提供することができる。 なお、本発明の積層体の製造方法は、特に包装材の製造に適したものである。
Smart Images

Figure 2025034554000001 
Figure 2025034554000002
Abstract
Description
[Technical field]
[0001] An embodiment of the present invention relates to a method for producing a laminate. Another embodiment of the present invention relates to a method for producing a molding material and a method for producing a molded body. [Background technology]
[0002] In recent years, packaging, plastic bottles, and other plastic products made from plastic film have been discarded or dumped as garbage in the ocean, causing environmental pollution. These plastic products break down in seawater and become submicron-sized fragments (microplastics), which float in the seawater. These microplastics are ingested by marine organisms such as fish and become concentrated in their bodies, raising concerns that they may affect the health of seabirds and humans who consume these marine organisms as food.
[0003] The plastic products include food packaging packages having a multi-layer structure using plastic films, and various plastic substrates such as polyester substrates, nylon substrates (NY), polypropylene substrates (PP), and polyethylene substrates (PE) are used as film substrates in such food packaging packages. These film substrates are printed with printing ink, bonded to other film substrates or heat-melting resin substrates via adhesives, and then cut and heat-sealed to form packages. However, such food packaging packages having a multi-layer structure contain multiple incompatible materials, and therefore have the problem that they cannot be recycled as they are.
[0004] Regarding material recycling of such multi-layered packaging materials, for example, Patent Documents 1 and 2 disclose a technology for removing printed layers not only from surface-printed laminates but also from multi-layered laminates by processing a laminate having a removal layer containing a polyurethane resin having a predetermined acid value.
[0005] Furthermore, Patent Document 3 discloses a technique for removing a printed layer from a laminate by treating the laminate, which includes a removal layer containing a hydroxyl-containing resin and an isocyanate-based curing agent, with alkaline water. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2020-090627 A [Patent Document 2] Patent Publication No. 2021-098294 [Patent Document 3] Patent Publication No. 2021-088408 Summary of the Invention [Problem to be solved by the invention]
[0007] However, in the manufacturing method of the laminate described in Patent Documents 1 to 3, when the printing layer is printed on the primer layer, a part of the primer layer is swollen and / or dissolved, and in particular in the case of overprinting rather than monochromatic printing, poor image quality of the printing layer such as a decrease in printing density and a decrease in reproducibility of the image occurs. Furthermore, the printing layer penetrates into the primer layer, so that the detachability in an alkaline aqueous solution decreases, and the detached printing layer is finely dispersed, so that the problem occurs that it is easily reattached to the substrate. And the molding material obtained by recycling such a substrate causes a decrease in appearance and physical properties due to coloring.
[0008] The object of the present invention is to provide a method for producing a laminate suitable for plastic recycling, which has excellent image quality and detachability of the printed layer and suppresses re-adhesion of detached components; to provide a method for producing a molding material obtained by melt-kneading recovered plastic base material; and to provide a method for producing a high-quality molded body obtained by hot-molding the molding material. [Means for solving the problem]
[0009] The present invention relates to the following [1] to
[10] .
[0010] [1] A method for producing a laminate having at least a plastic substrate, a primer layer containing a structural unit derived from a curing agent, and a printed layer in this order, comprising the steps of: A primer layer forming step of providing the primer layer on the plastic substrate; an aging step of aging the primer layer after the primer layer forming step such that a remaining rate of a peak derived from a curing agent measured by a Fourier transform infrared spectrophotometer (FT-IR) is 20% or less; A printing layer forming step of providing the printing layer on the primer layer after the aging step, The method for producing a laminate, wherein the primer layer is a layer that can be removed in a removing liquid in order to recover the plastic substrate.
[0011] [2] The method for producing a laminate according to [1], wherein the curing agent is a polyisocyanate compound.
[0012] [3] The method for producing a laminate according to [1], wherein the curing agent is a carbodiimide compound.
[0013] [4] The method for producing a laminate according to any one of [1] to [3], wherein the primer layer contains a compound that dissolves or swells in an alkaline aqueous solution.
[0014] [5] The method for producing a laminate according to [4], wherein the compound that dissolves or swells in an alkaline aqueous solution has an acidic group.
[0015] [6] The method for producing a laminate according to any one of [1] to [5], wherein the plastic substrate is a polyolefin substrate.
[0016] [7] A method for producing the laminate according to any one of [1] to [6], which is used for producing a packaging material.
[0017] [8] A method for separating and recovering a plastic substrate, comprising contacting a laminate obtained by the method for producing a laminate according to any one of [1] to [7] with a release liquid to release and recover the plastic substrate.
[0018] [9] A method for producing a molding material, comprising melt-kneading the plastic substrate recovered by the method for separating and recovering plastic substrates according to [8].
[0019]
[10] A method for producing a molded body, comprising hot molding a molding material obtained by the method for producing a molding material according to [9]. Effect of the Invention
[0020] According to the present invention, a method for producing a laminate suitable for plastic recycling, which has excellent image quality and detachability of a printed layer and suppresses reattachment of detached components, can be provided. Furthermore, a method for producing a molding material obtained by melt-kneading a recovered plastic base material, and a method for producing a high-quality molded product obtained by hot-molding the molding material can be provided. The method for producing a laminate of the present invention is particularly suitable for producing packaging materials. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The following describes in detail the embodiments of the present invention. However, the following description of the embodiments or requirements is merely an example of the embodiments of the present invention, and the present invention is not limited to these contents as long as it does not deviate from the gist of the present invention.
[0022] The method for producing a laminate of the present invention is a method for producing a laminate having at least a plastic substrate, a primer layer containing a structural unit derived from a curing agent, and a printed layer in this order, comprising the steps of: A primer layer forming step of providing the primer layer on the plastic substrate; The method for producing a laminate includes an aging step of aging the primer layer after the primer layer-forming step such that a residual rate of a peak derived from a curing agent measured by a Fourier transform infrared spectrophotometer (FT-IR) is 20% or less, and a printing layer-forming step of providing the printing layer on the primer layer after the aging step, wherein the primer layer is a layer that can be removed in a release liquid in order to recover the plastic substrate.
[0023] <Laminate> The laminate produced by the production method of the present invention includes at least a plastic substrate, a primer layer, and a printed layer in this order. The primer layer is removed by a release liquid described later, which allows the plastic substrate to be recovered and recycled.
[0024] <Laminate structure> Examples of laminate configurations are given below, but are not limited to these. In the following configurations, the "plastic substrate" and the "substrate" do not have to be a single layer, and may be a laminate of multiple substrates. Plastic substrate / Primer layer / Printing layer ·Plastic substrate / Primer layer / Printing layer / Adhesive layer / Plastic substrate ·Plastic substrate / Primer layer / Printed layer / Adhesive layer / Vapor deposition layer / Plastic substrate
[0025] In the laminate, the primer layer contains a structural unit derived from a curing agent, and a printed layer is printed on the primer layer after the aging process of the primer layer, thereby forming a laminate with excellent image quality of the printed layer. Furthermore, the primer layer is sufficiently crosslinked before the formation of the printed layer, which improves the detachment property and suppresses the detached components from being finely dispersed in the detachment liquid, thereby suppressing the detached printed layer and the like from reattaching to the substrate after detachment, and the substrate can be recovered without coloring or staining, and can be recycled into a high-quality regenerated material.
[0026] <Primer layer formation process> The method for producing a laminate of the present invention includes a primer layer forming step of providing a primer layer on a plastic substrate. The method of providing a primer layer on a plastic substrate is preferably printing. As the printing method, gravure printing, flexographic printing, screen printing, offset printing, dry offset printing, inkjet printing, etc. can be suitably used. Among them, gravure printing or flexographic printing is more preferable.
[0027] [Gravure printing] (Photogravure version) A gravure plate is a cylindrical metal plate, and recesses for each color are created by engraving, etching, or laser. There are no restrictions on the use of engraving and laser, and they can be set arbitrarily to match the pattern. Lines per page are appropriately set at 100 to 300 lines, and the higher the line count, the finer the printing. The thickness of the printing layer is preferably 0.1 μm to 100 μm.
[0028] (printing machine) In a gravure printing press, one printing unit is equipped with the gravure plate and doctor blade. There are many printing units, and printing units corresponding to organic solvent-based printing inks and picture inks can be set, and each unit has an oven drying unit. Printing is performed by rotary printing, and a roll-to-roll printing method is used. The type of plate and the type of doctor blade are selected appropriately according to the specifications.
[0029] [Flexographic printing] (Flexographic plate) Plates used in flexographic printing include photosensitive resin plates that use ultraviolet light curing from a UV light source, and elastomer material plates that use a direct laser engraving method. Regardless of the method used to form the image area of the flexographic plate, a plate with a screening line count of 75 lpi or more is used. Any sleeve or cushion tape can be used to attach the plate.
[0030] (printing machine) Flexographic printing machines include CI type multi-color flexographic printing machines and unit type multi-color flexographic printing machines, and ink supply methods include chamber methods and two-roll methods, and an appropriate printing machine can be used.
[0031] The thickness of the primer layer is preferably in the range of 0.5 to 10.0 μm, more preferably 0.6 to 5.0 μm, and further preferably 0.8 to 3.0 μm, and can be formed by using a known method.
[0032] <Primer layer> The primer layer in the embodiment of the present invention is a layer that is arranged in contact with the plastic substrate and can be removed from the plastic substrate by a known release liquid, and contains a structural unit derived from a curing agent. The primer layer contains a structural unit derived from a curing agent, and the printed layer is formed after a crosslinked structure is formed by an aging process of the primer layer, thereby suppressing the penetration of the printed layer into the primer layer and bleeding, and achieving excellent image quality. In addition, the release property is improved, and reattachment of the detached printed layer is prevented, and a high-quality recycled material can be obtained. In the present invention, the term "structural units derived from a curing agent" includes both the structural units before and after the curing agent has reacted with another compound.
[0033] [Hardening agent] Examples of the curing agent include a compound containing an isocyanate group, a compound containing a carbodiimide group, a compound containing an oxazoline group, a compound containing a hydrazide group, and an epoxy compound. Among them, a compound containing an isocyanate group (isocyanate-based curing agent) and a compound containing a carbodiimide group (carbodiimide-based curing agent) are preferred. These may be used alone or in combination of two or more kinds.
[0034] (Isocyanate-based hardener) The isocyanate-based curing agent is not particularly limited and can be selected from conventionally known isocyanate-based curing agents, for example, aliphatic polyisocyanates or aromatic aliphatic polyisocyanates. These may be used alone or in combination of two or more kinds.
[0035] As the aliphatic polyisocyanate, well-known aliphatic diisocyanates, alicyclic diisocyanates, araliphatic diisocyanates, or derivatives thereof can be used. Examples of the aliphatic diisocyanate include aliphatic diisocyanates such as trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, 1,2-propylene diisocyanate, 1,2-butylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, 2,4,4- or 2,2,4-trimethylhexamethylene diisocyanate, and 2,6-diisocyanate methyl caproate; 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), and methyl cyclohexyl isocyanate. alicyclic diisocyanates such as methyl 2,4-cyclohexane diisocyanate, methyl 2,6-cyclohexane diisocyanate, 1,4-bis(isocyanatomethyl)cyclohexane, and 1,3-bis(isocyanatomethyl)cyclohexane; araliphatic diisocyanates such as 1,3- or 1,4-xylylene diisocyanate or a mixture thereof, ω,ω'-diisocyanato-1,4-diethylbenzene, 1,3- or 1,4-bis(1-isocyanato-1-methylethyl)benzene or a mixture thereof; and polyisocyanates such as allophanate-type, nurate-type, biuret-type, and adduct-type derivatives derived from the above diisocyanates, or complexes thereof.
[0036] As the aromatic polyisocyanate, a well-known aromatic diisocyanate or a derivative thereof can be used. Examples of the aromatic diisocyanate include toluene diisocyanate, diphenylmethane diisocyanate, and allophanate, nurate, biuret and adduct derivatives derived from the above diisocyanates, or complexes thereof.
[0037] The polyisocyanate is preferably tolylene diisocyanate (hereinafter referred to as TDI), diisocyanate, The polyisocyanate is an adduct polyisocyanate (hereinafter, adduct form), a biuret polyisocyanate (hereinafter, biuret form), or an isocyanurate polyisocyanate (hereinafter, isocyanurate form) of phenylmethane diisocyanate (hereinafter, MDI) or hexamethylene diisocyanate (hereinafter, HDI), and more preferably a trimethylolpropane adduct (HDI-TPM), a biuret form, or an isocyanurate form derived from hexamethylene diisocyanate.
[0038] (Carbodiimide curing agent) The carbodiimide-based curing agent constituting the primer layer is not particularly limited and can be selected from conventionally known polyisocyanates, for example, monocarbodiimide compounds or bicarbodiimide compounds. These may be used alone or in combination of two or more kinds.
[0039] Examples of monocarbodiimide compounds include dicyclohexylcarbodiimide, diisopropylcarbodiimide, dimethylcarbodiimide, diisobutylcarbodiimide, dioctylcarbodiimide, t-butylisopropylcarbodiimide, dodecylisopropylcarbodiimide, diphenylcarbodiimide, di-o-tolylcarbodiimide, di-p-tolylcarbodiimide, cyanamide, di-t-butylcarbodiimide, 1,3-bis(trimethylsilyl)carbodiimide, di-β-naphthylcarbodiimide, and benzylisopropylcarbodiimide.
[0040] Polycarbodiimide compounds are produced by known methods, for example, by heating mono-, di-, or triisocyanate compounds in a non-reactive organic solvent in the presence of a suitable catalyst, such as 3-methyl-1-phenyl-2-phosphorate oxide, to convert the isocyanate group into a carbodiimide group by decarbonation. Organic isocyanates, which are raw materials for synthesizing polycarbodiimide compounds, include aromatic diisocyanates, aliphatic diisocyanates, alicyclic diisocyanates, or mixtures thereof, such as 1,5-naphthylene diisocyanate, 4,4-diphenylmethane diisocyanate, 4,4-diphenyldimethylmethane diisocyanate, 4,4-dibenzyl isocyanate, dialkyldiphenylmethane diisocyanate, and tetraalkyldiphenylmethane diisocyanate. , 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, tolylene diisocyanate, butane-1,4-diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, cyclohexane-1,4-diisocyanate, xylylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane-4,4-diisocyanate, 1,3-bis(isocyanatemethyl)cyclohexane, methylcyclohexane diisocyanate, n-tetramethylxylylene diisocyanate, dimeryl diisocyanate, etc. These carbodiimide compounds can be used alone or in combination of two or more.
[0041] The content of the structural unit derived from the curing agent is preferably 0.1 to 15% by mass, more preferably 0.5 to 10% by mass, and further preferably 1 to 7% by mass, based on 100% by mass of the primer layer. When the content of the structural unit derived from the curing agent is within the above range, penetration and bleeding of the printing layer formed on the primer layer is suppressed, excellent image quality is exhibited, and the ability to suppress detachment and reattachment is also good, which is preferable.
[0042] The primer layer preferably contains a compound that dissolves or swells in an alkaline aqueous solution. The compound that dissolves or swells in an alkaline aqueous solution refers to the following water-soluble resin and / or a compound having an acidic group, and a compound having an acidic group is particularly preferred.
[0043] The primer layer is preferably a layer containing a water-soluble resin or a compound having an acidic group. It is presumed that the primer layer containing a water-soluble resin or a compound having an acidic group allows the release liquid to penetrate more and the primer layer to swell more easily, promoting the release of the substrate, resulting in a significantly increased release property of the printing layer. The compound having an acidic group may be a resin or a low molecular weight compound. These water-soluble resins or compounds having an acidic group may be used alone or in combination of two or more.
[0044] The above-mentioned primer layer may contain a resin component as a binding resin (hereinafter also referred to as a binder resin) which contains a water-soluble resin or a resin having an acidic group, or may contain both a binder resin and a low molecular weight compound having an acidic group.
[0045] (Water-soluble resin) The water-soluble resin may be any resin that can swell or dissolve in water and be removed from the plastic substrate. The water may be heated to a temperature of about 25 to 100° C. This allows the primer layer to be removed by water (including warm water). Such resins can be selected from known resins as long as they do not impair water solubility, and examples thereof include water-soluble polyester resins, water-soluble polyamide resins, water-soluble polyimide resins, water-soluble acrylic resins, water-soluble polyurethane resins, water-soluble polyallylamine resins, water-soluble phenolic resins, water-soluble epoxy resins, water-soluble phenoxy resins, water-soluble urea resins, water-soluble melamine resins, polyvinyl alcohol resins, and modified products of these resins. These can be used alone or in combination of two or more. Among them, polyvinyl alcohol (PVA) resins are preferably used from the viewpoints of availability and release properties. When the water-soluble resin has film-forming properties, the water-soluble resin may be used as the binder resin constituting the primer layer. Examples of the water-soluble resin include a resin that is water-soluble and has an acidic group, and a resin that is water-soluble and does not have an acidic group. The water-soluble resin may be, for example, a resin that is water-soluble and does not have an acidic group.
[0046] As the polyvinyl alcohol resin, in addition to unmodified polyvinyl alcohol, modified polyvinyl alcohol obtained by copolymerizing various monomers during the production of vinyl ester resin and saponifying the copolymer, or various post-modified polyvinyl alcohols obtained by introducing various functional groups into unmodified polyvinyl alcohol by post-modification may be used. Also, modified polyvinyl alcohols further modified may be used. These modifications may be performed within a range that does not impair the water solubility of the polyvinyl alcohol resin. These resins may be used alone or in combination of two or more.
[0047] As the polyvinyl alcohol resin, a resin containing a structural unit having a primary hydroxyl group in the side chain, or an ethylene-modified polyvinyl alcohol resin is preferable. Among them, a polyvinyl alcohol resin containing a structural unit having a primary hydroxyl group in the side chain is preferable because of its excellent melt moldability and excellent water solubility. The number of primary hydroxyl groups in these structural units is usually 1 to 5, preferably 1 to 2, and more preferably 1. In addition to the primary hydroxyl groups, it is preferable to have a secondary hydroxyl group. As the polyvinyl alcohol resin containing a structural unit having a primary hydroxyl group in the side chain, for example, a modified polyvinyl alcohol resin containing a 1,2-diol structural unit in the side chain is preferable.
[0048] In an embodiment of the present invention, the saponification degree of the polyvinyl alcohol resin (measured according to JIS K 6726) is usually 60 to 100 mol%. The preferred range of the saponification degree varies depending on the modified species. For example, in the case of an unmodified polyvinyl alcohol resin, it is usually 60 to 99.9 mol%, preferably 70 to 99.0 mol%, more preferably 75 to 98.5%. The saponification degree of the modified polyvinyl alcohol resin containing a side chain 1,2-diol structural unit is usually 60 to 99.9 mol%, preferably 65 to 99.8 mol%, more preferably 70 to 99.5 mol%. If the saponification degree is too low, the water solubility tends to decrease. The saponification degree of the ethylene-modified polyvinyl alcohol resin modified with a small amount of ethylene is usually 60 mol% or more, preferably 70 to 99.5 mol%, particularly preferably 75 to 99.0 mol%. The saponification degree within the above range is preferable because it provides excellent water solubility and good releasability, and is also preferable because it provides excellent coatability when forming a primer layer.
[0049] The average degree of polymerization of the polyvinyl alcohol resin (measured in accordance with JIS K 6726) is usually 100-3,000, preferably 150-2,000, more preferably 180-1,000, and particularly preferably 200-800.
[0050] (Compounds having an acidic group) The compound having an acidic group may be a resin having an acidic group or a low molecular weight compound having an acidic group. This allows the primer layer to be detached with a basic aqueous solution described below. Examples of the resin having an acidic group include a water-soluble resin having an acidic group and a water-insoluble resin having an acidic group. The resin having an acidic group may be, for example, a water-soluble resin or an insoluble resin as long as it has an acidic group.
[0051] Examples of resins having an acidic group include cellulose resins, urethane resins, polyamide resins, vinyl chloride / vinyl acetate copolymers, ketone resins, polyester resins, and (meth)acrylic resins. Examples of the acidic group include a carboxy group, a phosphate group, a sulfo group, a sulfino group, or an ester or salt thereof. Furthermore, as the resin having an acidic group, a rosin-modified resin having an acid value, such as maleic rosin or fumaric rosin, can be used. In addition, examples of resins having an acidic group that can be used include radical copolymers such as styrene-(meth)acrylic resins, styrene-maleic acid (anhydride) resins, and terpene-maleic acid (anhydride) resins, which are copolymerized with polymerizable monomers having an acidic group, such as polymerizable monomers having a carboxy group, such as itaconic acid, maleic acid, fumaric acid, and cinnamic acid; polymerizable monomers which are acid anhydrides, such as itaconic acid anhydride and maleic acid anhydride; polymerizable monomers having a sulfonic acid group, such as sulfonated styrene; and polymerizable monomers having a sulfonamide group, such as vinylbenzenesulfonamide; and acid-modified polyolefin resins. These may be used alone or in combination of two or more.
[0052] The low molecular weight compound having an acidic group refers to a compound that does not have a molecular weight distribution and has a molecular weight of 1,000 or less. Examples of such compounds include saturated fatty acids such as lauric acid, myristic acid, palmitic acid, margaric acid, and stearic acid; unsaturated fatty acids such as oleic acid, linoleic acid, linolenic acid, arachidonic acid, eicosapentaenoic acid, docosahexaenoic acid, and sorbic acid; hydroxy acids such as lactic acid, malic acid, and citric acid; aromatic carboxylic acids such as benzoic acid, phthalic acid, isophthalic acid, terephthalic acid, salicylic acid, gallic acid, mellitic acid, and cinnamic acid; dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, fumaric acid, and maleic acid; tricarboxylic acids such as aconitic acid; oxocarboxylic acids such as pyruvic acid and oxaloacetic acid; carboxylic acid derivatives such as amino acids and nitrocarboxylic acids; and acid anhydrides such as trimellitic anhydride and pyromellitic anhydride. The low molecular weight compound having an acidic group can be used in combination with the above-mentioned resin having an acidic group or a known binder resin constituting a known primer layer to form a primer layer.
[0053] From the viewpoint of recoatability, the primer layer preferably contains a compound having an acidic group. Also, from the viewpoint of printability, the primer layer preferably contains a urethane resin having an acidic group, an acrylic resin having an acidic group, or a rosin-modified resin. The primer layer may contain one of these resins alone or two or more of them in combination.
[0054] [Urethane resin having acidic groups] The urethane resin having an acidic group is not particularly limited, and examples thereof include a urethane resin obtained by reacting a polyol having an acidic group with a polyisocyanate, a resin obtained by acid-modifying hydroxyl groups in a urethane resin obtained by reacting a polyol with a polyisocyanate, and a resin obtained by acid-modifying amino groups in a urethane urea resin obtained by reacting a polyamine with an isocyanate group in a urethane resin obtained by reacting a polyol with a polyisocyanate. In addition, as the urethane resin having an acidic group, a resin obtained by reacting a polyol containing a hydroxy acid with a polyisocyanate may be used. By using a hydroxy acid as the polyol, it is possible to impart an acid value derived from a carboxy group to the urethane resin, and it is possible to improve the releasability. In addition, when the urethane resin having an acidic group has an isocyanate group, a polyamine may be reacted with a part of the isocyanate group to introduce a urea bond, thereby forming a urethane urea.
[0055] Polyol Polyol is a general term for a compound having at least two hydroxyl groups in one molecule. The number average molecular weight of the polyol is preferably 500 to 10,000, more preferably 1,000 to 5,000. The number average molecular weight is calculated from the hydroxyl value of the polyol, and the hydroxyl value refers to a value measured according to JIS K 0070. When the number average molecular weight of the polyol is 500 or more, the flexibility of the primer layer is excellent and the adhesion to the plastic substrate is improved. When the number average molecular weight is 10,000 or less, the blocking resistance to the plastic substrate is excellent.
[0056] The polyol is not particularly limited, and more preferably, at least one polyol selected from the group consisting of polyester polyol, polyether polyol, and polycarbonate polyol is used. The polyol may further include other dimer diol, hydrogenated dimer diol, castor oil modified polyol, etc. That is, the urethane resin preferably contains a structural unit derived from at least one polyol selected from the group consisting of polyester polyol, polyether polyol, and polycarbonate polyol. Since the ester bond site of the polyester polyol is hydrolyzed by alkali to improve the releasability, the urethane resin more preferably contains a structural unit derived from a polyester polyol. The content of the structural units derived from polyol is preferably 10 to 75% by mass, more preferably 15 to 70% by mass, and even more preferably 20 to 65% by mass, based on the total amount of the urethane resin. The content of the structural units derived from polyester polyol is preferably 5% by mass or more, more preferably 30% by mass or more, even more preferably 60% by mass or more, and particularly preferably 80% by mass or more, based on the total amount of the structural units derived from polyol.
[0057] Hydroxy acids The polyol may contain a hydroxy acid. The hydroxy acid refers to a compound having both a hydroxyl group, which is an active hydrogen group, and an acidic functional group in one molecule. The acidic functional group refers to a functional group that can be neutralized with potassium hydroxide when measuring the acid value, and specifically includes a carboxy group and a sulfonic acid group, and is preferably a carboxy group. As such a hydroxy acid, for example, dimethylolalkanoic acid such as 2,2-dimethylolpropionic acid, 2,2-dimethylolbutanoic acid, and 2,2-dimethylolvaleric acid is preferably used.
[0058] <Polyisocyanate> The polyisocyanate is not particularly limited and can be selected from conventionally known polyisocyanates. It preferably contains a diisocyanate or triisocyanate, and more preferably contains an aromatic, aliphatic or alicyclic diisocyanate. These may be used alone or in combination of two or more kinds.
[0059] Polyamines The polyamine for forming the urethane urea is not particularly limited, and is preferably a diamine compound. A diamine having a hydroxyl group may be used because it can introduce a hydroxyl group into the urethane resin.
[0060] The acid value of the urethane resin having an acidic group is preferably 15 mgKOH / g or more, more preferably 15 to 70 mgKOH / g, and even more preferably 20 to 50 mgKOH / g. If it is 15 mgKOH / g or more, the release property by the release liquid is improved, and if it is 70 mgKOH / g or less, the adhesion to the substrate and the retort resistance are improved, which are preferable. The hydroxyl value of the urethane resin is preferably 1 to 35 mgKOH / g, more preferably 10 to 30 mgKOH / g. If it is 1 mgKOH / g or more, the releasability by the release solution is improved, and if it is 35 mgKOH / g or less, the adhesion to the substrate is improved, which is preferable.
[0061] The weight average molecular weight of the urethane resin having an acidic group is preferably 10,000 to 100,000, more preferably 15,000 to 70,000, and even more preferably 15,000 to 50,000. The molecular weight distribution (Mw / Mn) of the urethane resin is preferably 6 or less. Mw represents the weight average molecular weight, and Mn represents the number average molecular weight. When the molecular weight distribution is 6 or less, the release property, drying property of the primer composition, and retort resistance are excellent. In addition, the smaller the molecular weight distribution, that is, the sharper the molecular weight distribution, the more uniform the dissolution or peeling action by the release liquid occurs, and the more the release property of the plastic substrate is improved. The molecular weight distribution is more preferably 5 or less, and even more preferably 4 or less. In addition, the molecular weight distribution is preferably 1.5 or more, and more preferably 1.2 or more. In this specification, Mw, Mn and molecular weight distribution (Mw / Mn) are polystyrene equivalent values determined by gel permeation chromatography (GPC).
[0062] The urethane resin having an acidic group may have an amine value. When the urethane resin has an amine value, the amine value is preferably 0.1 to 20 mgKOH / g, and more preferably 1 to 10 mgKOH / g. When the amine value is within the above range, the adhesion to the substrate is excellent.
[0063] The number of urethane bonds in the polyurethane resin having an acidic group is preferably 1 to 3 mmol / g, more preferably 1.5 to 2 mmol / g. The number of urea bonds is preferably 0 to 3 mmol / g, more preferably 0.2 to 1 mmol / g. The total number of urethane bonds and urea bonds is preferably 1 to 6 mmol / g, more preferably 1.7 to 3 mmol / g. By setting the number of urethane bonds and the number of urea bonds within the corresponding range, the releasability and the anti-reattachment properties are improved.
[0064] [Acrylic resin having acidic group] Examples of acrylic resins having an acidic group include polymers obtained by polymerizing a monomer containing a (meth)acrylic monomer having an acidic group, such as (meth)acrylic acid or maleic acid; and resins obtained by polymerizing a monomer containing a (meth)acrylic monomer having a hydroxyl group or a glycidyl group, and then modifying the functional group to introduce a carboxyl group (e.g., maleic anhydride modified resin). The acid value of the acrylic resin having an acidic group is preferably 50 mgKOH / g or more, and more preferably 100 mgKOH / g or more.
[0065] [Rosin-modified resin] Rosin-modified resins are resins prepared using rosin as one of the raw materials. Rosin contains a mixture of resin acids such as abietic acid, palustric acid, isopimaric acid, and levopimaric acid, and these resin acids contain hydrophilic and chemically active carboxyl groups, some of which have conjugated double bonds. For this reason, various rosin-modified resins are prepared by combining polyhydric alcohols and polybasic acids and polycondensing them, adding resol, which is a condensate of phenol, to the benzene ring contained in the rosin skeleton, or by carrying out a Diels-Alder reaction with maleic anhydride or maleic acid, which is a dienophile, to add maleic acid or maleic anhydride skeletons. Various types of such rosin-modified resins are commercially available, and it is also possible to obtain and use them.
[0066] Examples of rosin-modified resins include maleated rosin, fumarated rosin, rosin-modified maleic acid resin, rosin-modified fumaric acid resin, rosin-modified phenolic resin, rosin-modified alkyd resin, and rosin-modified polyester resin. In the embodiment of the present invention, any rosin-modified resin may be used, but among these, those containing in their structure a moiety derived from at least one selected from the group consisting of maleic acid, maleic anhydride, fumaric acid, and fumaric anhydride are preferably used. A resin "containing in its structure a moiety derived from at least one selected from the group consisting of maleic acid, maleic anhydride, fumaric acid, and fumaric anhydride" is one prepared using at least one selected from the group consisting of maleic acid, maleic anhydride, fumaric acid, and fumaric anhydride as part of a raw material, and means, for example, a rosin-modified maleic acid resin or rosin-modified fumaric acid resin obtained by condensation polymerization of maleic acid or fumaric acid as part of a polybasic acid, a maleated rosin or fumarated rosin having a structure in which maleic acid, maleic anhydride, fumaric acid, or fumaric anhydride is added as a dienophile by a Diels-Alder reaction, or a resin obtained by further polymerizing other chemical species using the functional groups contained in these.
[0067] The acid value of the rosin-modified resin is preferably from 10 to 400 mgKOH / g, and more preferably from 100 to 300 mgKOH / g.
[0068] (Other ingredients) The primer layer may contain a resin other than the water-soluble resin or the compound having an acidic group. Examples of such resins include cellulose resins, polyamide resins, vinyl chloride resins such as vinyl chloride-vinyl acetate copolymer resins or vinyl chloride-acrylic copolymer resins, ethylene-vinyl acetate copolymer resins, vinyl acetate resins, acrylic resins, styrene resins, dammar resins, styrene-acrylic copolymer resins, polyester resins, alkyd resins, terpene resins, phenol-modified terpene resins, ketone resins, cyclized rubbers, chlorinated rubbers, butyral, polyacetal resins, petroleum resins, and modified resins thereof. These resins may be used alone or in combination of two or more. Among them, the primer layer preferably contains at least one resin selected from the group consisting of cellulose resin, vinyl chloride resin, rosin resin, and acrylic resin, and more preferably contains vinyl chloride resin or acrylic resin. The mass ratio of the urethane resin having an acidic group to the other resins (urethane resin having an acidic group:other resins) is preferably 95:5 to 50:50. When the mass ratio is within the above range, the printed layer is peeled off in a thin film state when peeled off together with the primer layer in a basic aqueous solution, which is preferable because recovery is easy.
[0069] The primer layer may contain a body pigment. Examples of the body pigment include silica, barium sulfate, kaolin, clay, calcium carbonate, magnesium carbonate, zinc oxide, zirconium oxide, and other metal oxides. Among these, silica is preferred, and hydrophilic silica is more preferred. The average particle size of the extender pigment is preferably 0.5 to 10 μm, more preferably 1 to 8 μm. The content of the extender pigment in the primer layer is preferably 0.5 to 10 mass %, more preferably 1 to 5 mass %. When the average particle size and the content of the extender pigment are within the above ranges, the wettability of the printing layer is improved, and the image quality is improved.
[0070] The primer layer may further contain known additives, such as dispersants, wetting agents, adhesion promoters, leveling agents, defoamers, antistatic agents, viscosity modifiers, metal chelates, trapping agents, antiblocking agents, wax components other than those mentioned above, and silane coupling agents.
[0071] <Aging process> The method for producing the laminate of the present invention includes, after a primer layer-forming step, an aging step of aging the primer layer such that the remaining rate of a peak derived from a curing agent measured with a Fourier transform infrared spectrophotometer (FT-IR) is 20% or less. The residual rate is calculated by the following formula. Residual rate (%) = (peak area derived from the curing agent in the primer layer after aging) / (peak area derived from the curing agent in the primer layer immediately after coating) If the residual rate is 20% or less, the printing layer can prevent the primer layer from swelling and dissolving, and a printed matter with excellent image quality can be obtained, while at the same time improving the release and reattachment properties in the release liquid, and a high-quality recycled material can be obtained. The residual rate is preferably 15% or less, more preferably 10% or less, and even more preferably 5% or less.
[0072] The aging temperature is preferably 20°C to 100°C, more preferably 20°C to 70°C, and even more preferably 25°C to 50°C. The aging time is preferably 1 hour to several days, more preferably 3 hours to 2 days, and even more preferably 6 hours to 24 hours. The aging time can be shortened as the aging temperature is higher, but from the viewpoint of blocking and the like, the aging temperature is preferably 50°C or less. When aging is performed at 25°C, the aging time is preferably 3 hours to several days, more preferably 6 hours to 2 days, and even more preferably 12 hours to 24 hours.
[0073] <Print layer formation process> The method for producing the laminate of the present invention includes a printing layer forming step of providing a printing layer on the primer layer after the aging step. The printing method for providing the printing layer can be the same as that described in the above section <Primer layer forming step>.
[0074] <Print layer> The printed layer is a layer provided in contact with the primer layer on the side opposite to the plastic substrate of the primer layer. The printed layer is a layer on which any printed pattern is formed for the purpose of decoration, imparting aesthetic appeal, displaying contents, expiration date, manufacturer or seller, etc., and includes a solid printed layer. The printed layer can be formed using a conventionally known colorant, and may be formed using a printing ink containing a pigment or dye. The printed layer may be a single layer or may be formed of multiple layers.
[0075] (Coloring agent) The printing layer may be colored or colorless, and contains a known colorant used in printing inks and paints. Such colorants are not particularly limited, and may include inorganic pigments, organic pigments, dyes, metal powders that impart metallic luster, near-infrared absorbing materials, and ultraviolet absorbing materials. Examples of inorganic pigments include color pigments such as titanium oxide, red iron oxide, Prussian blue, ultramarine blue, carbon black, and graphite; and extender pigments such as calcium carbonate, kaolin, clay, barium sulfate, aluminum hydroxide, and talc. As the organic pigment, a soluble azo pigment, an insoluble azo pigment, an azo lake pigment, a condensed azo pigment, a copper phthalocyanine pigment, a condensed polycyclic pigment, etc. are suitably used. However, the pigment is not limited to these, and any pigment listed by its generic name in the Color Index can be used as appropriate. Among them, when the release solution is a basic aqueous solution, a pigment that is not eluted in the basic aqueous solution and has alkali resistance is preferred. Preventing the elution of the pigment makes it easy to reuse the basic aqueous solution. The alkali resistance of a pigment is generally estimated based on the skeleton or structure of the pigment. Examples of alkali-resistant pigments include inorganic pigments, CI Pigment Blue 15, and CI Pigment Yellow 83. When the pigment is titanium oxide, the content of titanium oxide in the printed layer is preferably 20 to 80% by mass, more preferably 30 to 75% by mass. When the pigment is an inorganic pigment other than titanium oxide, an extender pigment, or an organic pigment, the content of each of these pigments in the printed layer is preferably 0.5 to 60% by mass, more preferably 10 to 50% by mass.
[0076] (Other ingredients) The print layer may contain a pigment derivative or a resin-type dispersant as a dispersant for the colorant. The pigment derivative is a compound in which a substituent has been introduced into the skeleton of a pigment, and the content of the pigment derivative is preferably 0.01 to 10 mass%, more preferably 0.05 to 6 mass%, and even more preferably 0.1 to 4 mass%, based on the mass of the colorant. When it is 0.01 mass% or more, it is possible to provide excellent releasability from the plastic substrate, and when it is 10 mass% or less, it is possible to suppress reattachment of the printed layer. The resin-type dispersant functions to adsorb to the colorant and stabilize the dispersion in the printing ink, etc., and can be appropriately selected from known resin-type dispersants. The content of the resin-type dispersant is preferably 0.01 to 30 mass%, more preferably 0.05 to 20 mass%, and even more preferably 0.1 to 10 mass%, based on the mass of the colorant. When it is 0.01 mass% or more, the releasability of the plastic substrate is excellent, and when it is 30 mass% or less, the water resistance of the printed layer is excellent.
[0077] The printing layer may contain a binder resin. Examples of such resins include nitrocellulose-based, cellulose acetate-propionate and other fiber materials, chlorinated polypropylene-based, vinyl chloride-vinyl acetate copolymer-based, polyester-based, acrylic, urethane resin-based and acrylic urethane-based, polyamide-based, polybutyral-based, cyclized rubber-based, and chlorinated rubber-based resins. These resins may be used alone or in combination of two or more. The printing layer may contain a water-soluble resin or a compound containing an acidic group. In this case, the printing layer also has releasability in the release liquid.
[0078] The thickness of the printing layer is preferably 0.1 μm or more and 100 μm or less, more preferably 0.1 μm or more and 10 μm or less, and even more preferably 1 μm or more and 5 μm or less.
[0079] <Plastic substrate> Examples of the plastic substrate include polyolefin resin, polyester resin, polyamide resin, polystyrene resin, vinyl chloride resin, vinyl acetate resin, ABS resin, acrylic resin, acetal resin, polycarbonate resin, polyvinyl alcohol resin, and cellulose-based plastics.
[0080] From the viewpoint of reuse as a recycled substrate, the plastic substrate is preferably a polyolefin substrate containing a polyolefin resin. Examples of substrates containing such polyolefin resin include plastic substrates such as polyethylene (PE) and biaxially oriented polypropylene (OPP), as well as sealant substrates such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), high-density polyethylene (HDPE), acid-modified polyethylene, non-oriented polypropylene (CPP), acid-modified polypropylene, and copolymer polypropylene.
[0081] The thickness of the plastic substrate is not particularly limited and may be appropriately selected depending on the application. It is preferably 5 to 200 μm, more preferably 10 to 150 μm. In addition, examples of gas barrier substrates include aluminum foil, a metal vapor deposition layer such as aluminum, and a metal oxide vapor deposition layer such as silica or alumina. The thickness of the aluminum foil is often used in the range of 3 to 50 μm from an economical point of view. In addition, the aluminum foil, the aluminum vapor deposition layer, and the alumina vapor deposition layer dissolve and are released in a basic aqueous solution, so they function as a release layer and can separate adjacent polyolefin resins.
[0082] <Adhesive layer> The laminate may include an adhesive layer. When the laminate includes an adhesive layer, the adhesive layer preferably contains a compound containing an acidic group in order to also separate and recover the plastic substrate in contact with the adhesive layer. For the compound having an acidic group, the resin having an acidic group, and the low molecular weight compound having an acidic group, the description of (Compound having an acidic group) in the above section <Primer layer> can be cited. The method for forming the adhesive layer is not limited, and the adhesive layer can be formed by using a known method.
[0083] From the viewpoint of releasability, the adhesive layer may be a cured product of an adhesive containing a polyester polyol having an acidic group and at least one polyisocyanate selected from the group consisting of an aliphatic polyisocyanate and an araliphatic polyisocyanate. The cured product corresponds to a resin having an acidic group. The adhesive layer may also be a cured product of an adhesive containing a polyester polyol, at least one polyisocyanate selected from the group consisting of aliphatic polyisocyanates and araliphatic polyisocyanates, and a low molecular weight compound having an acidic group.
[0084] <Method for separating and recovering plastic substrates> An embodiment of the present invention includes a method for separating and recovering a plastic substrate, in which the laminate obtained by the laminate manufacturing method of the present invention is contacted with a release liquid described below, and the plastic substrate is released and recovered. In the present invention, "release" refers to, for example, the release layer being dissolved or swollen by the release liquid and peeled off, thereby causing the substrate to be released from the laminate, and includes both cases: (1) the release layer is dissolved and the substrate is released, and (2) even if the release layer is not dissolved, the substrate is released due to neutralization or swelling, etc., and the substrate is released. For example, the separation and recovery method may include removing the substrate from the laminate and recovering the substrate. In the present invention, "detachment" may refer to, for example, the detachment layer being dissolved or swelled by a detachment liquid and peeled off, thereby detaching the detachment layer from the laminate, and includes both cases, that is, (1') the case where the detachment layer is dissolved and detached, and (2') the case where the detachment layer is not dissolved but is peeled off and detached by neutralization or swelling, etc. For example, the separation and recovery method may include detaching the detachment layer from the laminate and recovering the substrate.
[0085] Since the present invention aims to obtain the plastic substrate after the detachment as a recycled substrate or a regenerated substrate, an embodiment in which the detachment layer and the like are removed from the plastic substrate as much as possible is preferable. Specifically, it is preferable that at least 50% by mass or more of the detachment layer is detached in the area or thickness direction out of 100% by mass of the detachment layer. More preferably, it is preferable that 60% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more is detached.
[0086] <Removal solution> The release liquid may be any liquid that swells and dissolves the primer layer, and examples of such release liquids include a neutral aqueous solution, a basic aqueous solution, an acidic aqueous solution, and a fluorine-based solvent. From the viewpoint of the environment and maintaining the properties of the recycled material using the recovered plastic substrate, an aqueous solution is preferable. From the viewpoint of release properties, a basic aqueous solution containing a basic compound is more preferable. These release liquids may be heated. The release liquid preferably contains 50% by mass or more of water, more preferably 70% by mass or more, and even more preferably 80% by mass or more.
[0087] [Surfactants] The release liquid preferably contains water and a surfactant. The surfactant mainly plays a role in improving the release property of the release layer. This is thought to be because the action of the surfactant makes it easier for the release liquid to penetrate into the primer layer, the printing layer, the adhesive layer, etc., and promotes the release property. In addition, it is thought that the surfactant is adsorbed on the surface of the released components and the substrate, thereby preventing reattachment of the finely dispersed printing layer, etc. In addition, when the amount of the laminate relative to the release liquid is increased during separation and recovery, the laminate and the separated substrate tend to curl with the detached ink particles wrapped around them, and it is difficult to completely remove the ink particles wrapped around the curl even when the laminate and the separated substrate are immersed in the release liquid. However, when the release liquid contains a surfactant, the surfactant is adsorbed on the surfaces of the laminate and the separated substrate, suppressing curling. As a result, the release property is improved and reattachment can be suppressed.
[0088] The HLB value is an index value relating to the affinity of a surfactant for water and oil, and is divided equally between an HLB value of 0 for a substance having no hydrophilic groups and an HLB value of 20 for a substance having only hydrophilic groups. The concept of HLB was proposed by William Griffin of the Atlas Powder Company in 1949, and several methods for determining HLB by calculation have been proposed, but in the embodiment of the present invention, the HLB value can be calculated from the following formula using the Griffin method. Formula) HLB = 20 x [(molecular weight of hydrophilic group contained in surfactant) / (molecular weight of surfactant)] Examples of the hydrophilic group contained in the surfactant include a hydroxyl group and an ethyleneoxy group.
[0089] The HLB value of the surfactant in the embodiment of the present invention is preferably 7 or more. With an HLB value of 7 or more, excellent releasability and anti-reattachment properties are exhibited as described above. The HLB value of the surfactant is preferably 8 or more, more preferably 10 or more. The HLB value of the surfactant is preferably 20 or less, more preferably 19 or less, and even more preferably 17 or less. An HLB value of 20 or less is preferable because it has excellent defoaming properties.
[0090] The type of surfactant may be, for example, nonionic, anionic, cationic, or amphoteric, and the type and amount of the surfactant may be appropriately selected according to the required properties. From the viewpoint of releasing property and foaming property, the surfactant is preferably at least one selected from the group consisting of anionic surfactants and nonionic surfactants. Moreover, the surfactant preferably has a structure with an alkylene oxide (hereinafter, also referred to as AO) added thereto, since this improves the releasing property and the preventing property of reattachment.
[0091] (Nonionic surfactant) The nonionic surfactant is not particularly limited, but is preferably an alkylene oxide adduct in which an alkylene oxide is added. More preferably, it is a compound obtained by adding an alkylene oxide to an alcohol having active hydrogen, a compound obtained by adding an alkylene oxide to an amine, or a compound obtained by adding an alkylene oxide to a fatty acid. The above addition may be either random addition or block addition. In addition, the number of carbon atoms of the alkylene oxide is preferably 2 to 4. The nonionic surfactant is more preferably an alcohol-based nonionic surfactant in which an alkylene oxide having 2 to 4 carbon atoms is added to an alcohol.
[0092] [Alcohol-based nonionic surfactant] Examples of the alcohol-based nonionic surfactant include alkylene oxide adducts of primary or secondary alcohols having a total of 8 to 24 carbon atoms, and alkylene oxide adducts of alkylphenols having a total of 8 to 12 carbon atoms. The primary or secondary alcohols having a total of 8 to 24 carbon atoms may be either saturated or unsaturated. Examples of the primary or secondary alcohol having a total of 8 to 24 carbon atoms include lauryl alcohol, stearyl alcohol, oleyl alcohol, dodecyl alcohol, arachidyl alcohol, behenyl alcohol, lignoceryl alcohol, and myristyl alcohol. Examples of the alkylene oxide added to the alcohol include ethylene oxide, propylene oxide, and butylene oxide, and it is preferable to use ethylene oxide as an essential component. The number of moles of the alkylene oxide added is preferably 1 to 100 moles, more preferably 2 to 50 moles, per mole of the alcohol or alkylphenol. The above range is preferable because it has excellent elimination properties.
[0093] [Fatty acid-based nonionic surfactant] The structure of the fatty acid-based nonionic surfactant is not particularly limited, and examples thereof include alkylene oxide adducts of higher fatty acids having a total of 10 to 24 carbon atoms, fats and oils consisting of esters of the above-mentioned saturated or unsaturated higher fatty acids having a total of 10 to 24 carbon atoms and glycerin, and further, alkylene oxide adducts of mixtures of the above-mentioned fats and oils and polyhydric alcohols having 2 to 10 carbon atoms. The above-mentioned higher fatty acids having a total of 10 to 24 carbon atoms may be either saturated or unsaturated. Examples of the higher fatty acid having a total carbon number of 10 to 24 include saturated higher fatty acids such as lauric acid, myristic acid, palmitic acid, stearic acid, arachic acid, and behenic acid; and unsaturated higher fatty acids such as palmitoleic acid, oleic acid, elaidic acid, linoleic acid, linolenic acid, erucic acid, and ricinoleic acid. Examples of the dihydric to decahydric polyhydric alcohol include ethylene glycol, propylene glycol, glycerin, polyglycerin, sorbitol, sorbitan, and sucrose. The type and molar number of the alkylene oxide are the same as those described in the above section on [Alcohol-based nonionic surfactants].
[0094] [Amine-based nonionic surfactant] Examples of the amine-based nonionic surfactant include AO adducts of saturated or unsaturated primary or secondary amines having a total carbon number of 8 to 36. Examples of the amine include 2-ethylhexylamine, di-2-ethylhexylamine, laurylamine, dilaurylamine, tetradecylamine, ditetradecylamine, hexadecylamine, dihexadecylamine, stearylamine, distearylamine, oleylamine, dioleylamine, etc. The type and number of moles of AO added are the same as above.
[0095] (anionic surfactant) The anionic surfactant is preferably a non-soap surfactant, and examples thereof include sulfonic acid-based anionic surfactants, sulfate ester-based anionic surfactants, carboxylate-based anionic surfactants, and phosphate ester-based anionic surfactants.
[0096] [Sulfonic acid-based anionic surfactant] Examples of the sulfonic acid anionic surfactant include alkylsulfonic acid, alkylbenzenesulfonic acid, alkylnaphthalenesulfonic acid, alkyldiphenyletherdisulfonic acid, alkylmethyltaurine, sulfosuccinic acid diester, alkylene oxide adduct of sulfonic acid, and salts thereof.Specific examples include hexanesulfonic acid, octanesulfonic acid, decanesulfonic acid, dodecanesulfonic acid, toluenesulfonic acid, cumenesulfonic acid, octylbenzenesulfonic acid, dodecylbenzenesulfonic acid, dinitrobenzenesulfonic acid, and lauryldodecylphenyletherdisulfonic acid.
[0097] [Sulfate ester-based anionic surfactants] Examples of the sulfate anionic surfactant include sulfate (alkyl ether sulfate), alkylene oxide adduct of sulfate, and salts thereof. Specific examples include lauryl sulfate, myristyl sulfate, and polyoxyethylene lauryl ether sulfate.
[0098] [Carboxylic acid type anionic surfactant] Examples of the carboxylic acid-based anionic surfactant include alkyl carboxylic acids, alkyl benzene carboxylic acids, alkylene oxide adducts of carboxylic acids, and salts thereof. Specific examples of the surfactant that can be used include lauric acid, myristic acid, palmitic acid, stearic acid, polyoxyethylene lauryl ether acetic acid, and polyoxyethylene tridecyl ether acetic acid.
[0099] [Phosphate-based anionic surfactant] Examples of the phosphate anionic surfactant include phosphate (alkyl ether phosphate), alkylene oxide adduct of phosphate, and salts thereof.Specific examples include octyl phosphate, lauryl phosphate, tridecyl phosphate, myristyl phosphate, cetyl phosphate, stearyl phosphate, polyoxyethylene octyl ether phosphate, polyoxyethylene lauryl ether phosphate, etc.
[0100] The anionic surfactant preferably has an alkyl group having 2 to 24 carbon atoms or an alkenyl group having 2 to 24 carbon atoms, and more preferably has an alkyl group having 8 to 18 carbon atoms. The alkyl group or the alkenyl group may be linear or branched. In addition, when the anionic surfactant is an alkylene oxide adduct, the alkylene oxide may be, for example, ethylene oxide, propylene oxide, or butylene oxide, with ethylene oxide being preferred. The number of moles of alkylene oxide added is preferably 1 to 12 moles, more preferably 1 to 8 moles, per mole of alcohol or alkylphenol. The above range is particularly preferred because of excellent releasability.
[0101] Examples of the salt constituting the anionic surfactant include metal salts such as sodium, potassium, magnesium, calcium, etc. These salts may be used alone or in combination of two or more. Among these, from the viewpoint of releasability and anti-reattachment properties, preferred anionic surfactants are sulfonate type and phosphate type, and more preferred are alkyl sulfonate, polyoxyalkylene alkyl ether sulfonate, polyoxyalkylene alkyl ether phosphate, etc.
[0102] (Cationic Surfactant) Examples of cationic surfactants include alkylamine salts and quaternary ammonium salts.Specific examples of usable surfactants include stearylamine acetate, trimethyl coconut ammonium chloride, trimethyl beef tallow ammonium chloride, dimethyldioleyl ammonium chloride, methyl oleyl diethanol chloride, tetramethyl ammonium chloride, lauryl pyridinium chloride, lauryl pyridinium bromide, lauryl pyridinium disulfate, cetyl pyridinium bromide, 4-alkyl mercaptopyridine, poly(vinylpyridine)-dodecyl bromide, and dodecyl benzyl triethyl ammonium chloride.
[0103] (Amphoteric surfactant) Examples of amphoteric surfactants include lauryl dimethylaminoacetate betaine, 2-alkyl-N-carboxymethyl-N-hydroxyethyl imidazolinium betaine, coconut oil fatty acid amidopropyl dimethylaminoacetate betaine, polyoctyl polyaminoethyl glycine, and imidazoline derivatives.
[0104] These surfactants may be used alone or in combination of two or more. The content of the surfactant having an HLB value of 7 or more in the release liquid is preferably in the range of 0.001 to 10 mass%, more preferably in the range of 0.005 to 7 mass%, further preferably 0.03 to 5 mass%, and still more preferably 0.05 to 3 mass%, based on the mass of the release liquid. A content of 0.001 mass% or more is preferable because of excellent release properties and anti-reattachment properties, and a content of 10 mass% or less is preferable from the viewpoint of defoaming properties.
[0105] [Antifoaming agent] In the embodiment of the present invention, it is also preferable that the release liquid further contains an antifoaming agent. By using the antifoaming agent in combination with the above-mentioned surfactant, good antifoaming properties can be exhibited without reducing the release property and the reattachment prevention property, and foaming caused by the surfactant can be suppressed. Examples of the antifoaming agent include silicone-based compounds and non-silicone-based compounds.
[0106] (Silicone compounds) Examples of the silicone-based compound include emulsion type, self-emulsifying type, oil type, oil compound type, and solvent type. The emulsion type is a silicone-based defoamer in which a silicone oil compound is emulsified with an activator to form an O / W type (oil in water type) emulsion. Examples of such antifoamers include "KM-89" and "KM-98" manufactured by Shin-Etsu Chemical Co., Ltd., "FC2913" and "SILFOAMSE47" manufactured by Asahi Kasei Wacker Silicone Co., Ltd., and "BYK-015" and "BYK-1640" manufactured by BYK Japan. The self-emulsifying type is a silicone-based defoamer that is 100% active ingredient and becomes an emulsion when diluted and mixed with water. Examples include "KS-540" and "X-50-1176" manufactured by Shin-Etsu Chemical Co., Ltd., and "SILFOAM SD670" and "SILFOAM SD850" manufactured by Wacker Asahi Kasei Silicones. Oil-type defoamers are 100% silicone oil defoamers that do not contain solvents or additives. Examples include "KM-89" and "KM-98" made by Shin-Etsu Chemical Co., Ltd., "AK350" and "AK12500" made by Asahi Kasei Wacker Silicone, and "BYK-1770" made by BYK Japan. Oil compound type is a silicone-based defoamer that combines silica particles with silicone oil. Examples include "KM-89" and "KM-98" manufactured by Shin-Etsu Chemical Co., Ltd., "SILFOAM SC370" and "PULPSIL22274VP" manufactured by Asahi Kasei Wacker Silicone, and "BYK-017" and "BYK-018" manufactured by BYK Japan. Solvent-type defoamers are silicone-based defoamers in which silicone oil is dissolved in a solvent. Examples include "KM-89" and "KM-98" manufactured by Shin-Etsu Chemical Co., Ltd., and "BYK-019" and "BYK-025" manufactured by BYK Japan.
[0107] (Non-silicone compounds) Examples of the non-silicone compounds include fatty acid ester compounds, urea resin compounds, paraffin compounds, polyoxyalkylene glycol compounds, acrylic ester copolymers, ester polymers, ether polymers, amide polymers, emulsion types of mineral oils, polysiloxane adducts, fluorine compounds, vinyl polymers, acetylene alcohol, acrylic polymers, special vinyl polymers, ethylene glycol, and higher alcohols (such as octyl alcohol and cyclohexanol).
[0108] The defoaming agent may be used alone or in combination of two or more. The content of the defoaming agent in the release liquid is preferably in the range of 0.0001 to 5 mass%, more preferably in the range of 0.001 to 4.5 mass%, further preferably in the range of 0.01 to 4 mass%, still more preferably in the range of 0.02 to 3.5 mass%, and particularly preferably in the range of 0.03 to 3 mass%, based on the mass of the release liquid. When it is 0.0001 mass% or more, the defoaming property is excellent, and when it is 5 mass% or less, the release property and the anti-reattachment property are excellent.
[0109] The above-mentioned defoaming agent is preferably at least one selected from the group consisting of emulsion-type silicone compounds, self-emulsifying silicone compounds, and non-silicone compounds, from the viewpoints that it has good alkali resistance and is unlikely to deteriorate releasability or anti-reattachment properties when combined with a surfactant.
[0110] [Basic compounds] As described above, in an embodiment of the present invention, the release liquid is preferably a basic aqueous solution containing a basic compound from the viewpoint of releasing a urethane adhesive layer that is typically used in packaging materials. The basic compound is not particularly limited, and for example, sodium hydroxide (NaOH), potassium hydroxide (KOH), calcium hydroxide (Ca(OH)2), ammonia, barium hydroxide (Ba(OH)2), and sodium carbonate (Na2CO3) are preferably used. More preferably, it is at least one selected from the group consisting of sodium hydroxide and potassium hydroxide. The content of the basic compound in the basic aqueous solution is preferably in the range of 0.5 to 20 mass%, more preferably 1 to 15 mass%, and further preferably 3 to 15 mass%, based on the mass of the basic aqueous solution. Within the above range, the basic aqueous solution can retain sufficient basicity to remove the detachment layer described below by dissolving or swelling, and recover the plastic substrate.
[0111] The release liquid penetrates the end of the laminate, contacts the release layer, and dissolves or swells, separating the plastic substrate from the release layer. Therefore, in order to efficiently proceed with the release step, it is preferable that the laminate is cut or crushed, and the release layer is exposed on the cross section when immersed in the release liquid. In such a case, the substrate layer can be released in a shorter time.
[0112] The content of the laminate when the laminate is separated in the desorption liquid is preferably 0.1% by mass or more and 10% by mass or less, more preferably 1% by mass or more and 8% by mass or less, further preferably 1.5% by mass or more and 7% by mass or less, and even more preferably 2% by mass or more and 6% by mass or less, based on the total mass of the desorption liquid. A content of 0.1% by mass or more is preferable from the viewpoint of processing efficiency. A content of 10% by mass or less is preferable from the viewpoint of desorption property.
[0113] The content of the printed layer when the laminate is separated in the release liquid is preferably 0.01% by mass or more, more preferably 0.05% by mass or more and 1% by mass or less, and even more preferably 0.1% by mass or more and 0.5% by mass or less, based on the total mass of the release liquid. 0.01% by mass or more is preferable from the viewpoint of processing efficiency. 1% by mass or less is preferable from the viewpoint of re-adhesion.
[0114] The temperature of the release liquid when the laminate is immersed is preferably in the range of 25 to 120°C, more preferably 30 to 120°C, and particularly preferably 30 to 80°C. The immersion time in the release liquid is preferably in the range of 1 minute to 24 hours, more preferably 1 minute to 12 hours, and preferably 1 minute to 6 hours. In order to improve the release efficiency, it is preferable to stir or circulate the release liquid. The rotation speed is preferably 80 to 5000 rpm, and more preferably 80 to 4000 rpm.
[0115] The detachment layer is detached from the laminate, and the plastic substrate is recovered, and the plastic substrate is washed with water and dried to obtain a recycled substrate. The removal rate of the detachment layer on the surface of the substrate is preferably 70% or more, more preferably 80% or more, and particularly preferably 90% or more, based on the area of the detachment layer before detachment. The resulting recycled base material can be processed into pellets using an extruder or the like and reused as recycled resin.
[0116] <Manufacturing method of plastic substrate> The plastic substrate can be manufactured using the above-mentioned separation and recovery method for the plastic substrate. The plastic substrate may be a substrate that has been fragmented by crushing, cutting, pulverization, or the like. The method for manufacturing the plastic substrate includes, for example, preparing a laminate that includes at least a plastic substrate layer and a detachment layer in contact with the plastic substrate layer, the detachment layer being a layer that contains a water-soluble resin or a compound having an acidic group, and recovering the plastic substrate by the above-mentioned separation and recovery method.
[0117] <Method of manufacturing molding material> A molding material can be produced by melt-kneading the plastic substrate recovered by the above-mentioned method for separating and recovering a plastic substrate. The method for producing a molding material according to an embodiment of the present invention preferably includes the following steps 1 to 3. Alternatively, the above-mentioned method for separating and recovering a plastic substrate or the method for producing a plastic substrate may include at least the following step 1, and the method for producing a molding material may include at least the following step 3. When the molding material includes a master batch, it may further include the following step 4. (Step 1) A step of crushing the laminate and immersing the laminate in a release liquid to remove the plastic substrate from the laminate, or a step of crushing the laminate and immersing the laminate in a release liquid to remove the release layer from the laminate. (Step 2) A step of washing the plastic substrate obtained in step 1 with water. (Step 3) A step of melt-kneading the plastic base material obtained in step 2 to obtain recycled resin. (Step 4) A step of mixing the master batch with the recycled resin obtained in step 3.
[0118] The method for crushing the packaging material in step 1 is not particularly limited, and examples thereof include methods using a jaw crusher, impact crusher, cutter mill, stamp mill, ring mill, roller mill, jet mill, and hammer mill. Step 2 may further include a drying step, if necessary. By step 2, a recycled substrate (also called a recycled plastic substrate) can be obtained.
[0119] The melt-kneading step in step 3 refers to adding various additives as necessary, mixing with a Henschel mixer, tumbler, disperser, etc., and then mixing and dispersing using a batch type kneader such as a kneader, roll mill, super mixer, Henschel mixer, Shugi mixer, vertical granulator, high-speed mixer, Farmatrix, ball mill, steel mill, sand mill, vibration mill, attritor, Banbury mixer, twin-screw extruder, single-screw extruder, rotor-type twin-screw kneader, etc. This results in a recycled resin, which is a resin composition. The shape of the recycled resin is not particularly limited and may be pellet-shaped, powder-shaped, granular, or bead-shaped. The melt-kneading step is preferably performed using a twin-screw extruder.
[0120] [Master batch] The molding material in the embodiment of the present invention may further contain a masterbatch. The masterbatch is not particularly limited as long as it has compatibility with the recycled resin, and generally, a mixture of a thermoplastic resin such as a polyethylene resin or a polypropylene resin and a colorant can be used. The thermoplastic resin contained in the masterbatch may be used alone or in combination of two or more kinds. The master batch in an embodiment of the present invention may contain a metal soap of an alkali metal, an alkaline earth metal, or zinc, hydrotalcite, a nonionic surfactant, a cationic surfactant, an anionic surfactant, an amphoteric surfactant, an antistatic agent, a flame retardant such as a halogen-based, phosphorus-based, or metal oxide, a lubricant such as ethylene bis alkyl amide, an antioxidant, an ultraviolet absorber, or a filler, as long as the effects of the present invention are not impaired.
[0121] <Method of manufacturing molded body> The molding material obtained by the above-mentioned method for producing a molding material can be heated and molded to obtain a molded article. The heating and molding method is not particularly limited, and examples thereof include injection molding, extrusion molding, blow molding, and compression molding. The molding material produced using the plastic base material recovered by the separation and recovery method according to the embodiment of the present invention is of high quality because the printing layer and the adhesive layer are detached, and reattachment of the detached components is further suppressed. It can be used in various fields such as home appliances, stationery, automobile parts, toys and sports goods, materials for medical, architectural or construction materials, etc.
Examples
[0122] Hereinafter, the present invention will be described in detail with reference to examples, but the present invention is not limited to these examples. In the present invention, parts and % represent parts by mass and mass %, respectively, unless otherwise noted.
[0123] <Molecular weight and molecular weight distribution> The weight average molecular weight (Mw), number average molecular weight (Mn), and molecular weight distribution (Mw / Mn) were measured by GPC (gel permeation chromatography) and determined as the converted molecular weight using polystyrene as a standard substance. The measurement conditions are shown below. GPC apparatus: Shodex GPC-104 manufactured by Showa Denko KK Columns: The following columns were connected in series and used. Two Shodex LF-404 manufactured by Showa Denko KK Shodex LF-G manufactured by Showa Denko KK Detector: RI (differential refractometer) Measurement conditions: Column temperature 40 °C Eluent: Tetrahydrofuran Flow rate: 0.3 mL / min
[0124] <Acid value, hydroxyl value> The acid value and hydroxyl value were measured according to the method described in JIS K 0070 (1992).
[0125] <FT-IR measurement> After printing the primer composition on the substrate, the remaining ratio of the peak derived from the curing agent was calculated by ATR measurement. The remaining ratio of the peak derived from the curing agent was calculated by taking the area of the peak derived from the curing agent immediately after printing the primer layer as 100% and calculating the ratio of the peak derived from the curing agent after aging. That is, the residual rate is calculated by the following formula. Residual rate (%) = (peak area derived from the curing agent in the primer layer after aging) / (peak area derived from the curing agent in the primer layer immediately after coating)
[0126] In the following examples, the peak A derived from the isocyanate-based curing agent is about 2260 cm -1 The peak B derived from the carbodiimide curing agent was approximately 2120 cm -1 The baseline for calculating the peak area A was 2320 cm -1 ~2360cm -1 The minimum point and 2150cm -1 ~2200cm -1 The baseline for calculating peak area B is defined as the line connecting the minimum points of 2150 cm -1 ~2180cm -1 The minimum point and 2050cm -1 ~2100cm -1 is defined as the line connecting the minimum points of The FT-IR measurement conditions were as follows: Equipment manufacturer: Thermo SCIENTIFIC Instrument name: Nicolet iS50 FT-IR Spectrometer Measurement mode: ATR method Crystal: Diamond ·Resolution: 4cm -1 Number of times: 32
[0127] <Synthesis of Resin for Primer Composition> [Synthesis Example 1-1] (Polyurethane Resin P1) In a reactor equipped with a reflux condenser, a dropping funnel, a gas inlet tube, a stirrer, and a thermometer, while introducing nitrogen gas, 152.2 parts of PPA (a polyester polyol composed of a polycondensation product of propylene glycol and adipic acid and having a number average molecular weight of 2,000), 15.2 parts of PPG (a polyether polyol composed of polypropylene glycol and having a number average molecular weight of 2,000), 13.6 parts of BD (1,4-butanediol), 99.8 parts of IPDI (isophorone diisocyanate), and 200 parts of NPAC (normal propyl acetate) were charged and reacted at 90°C for 5 hours to obtain a urethane prepolymer solution having an isocyanate group at the end. Next, a mixture of 19.2 parts of AEA (2-(2-aminoethylamino)ethanol) and 350 parts of IPA (isopropyl alcohol) was added dropwise at room temperature over 60 minutes, and then reacted at 70°C for 3 hours to obtain a polyurethane resin solution. NPAC was added to the resulting polyurethane resin solution to adjust the solid content, thereby obtaining a solution of polyurethane resin P1 having a solid content concentration of 30%, a weight average molecular weight of 27,000, Mw / Mn=3.1 and an acid value of 0.0 mgKOH / g.
[0128] [Synthesis Example 1-2] (Polyurethane Resin P2) In a reactor equipped with a reflux condenser, a dropping funnel, a gas inlet tube, a stirrer, and a thermometer, 135.7 parts of PPA, 13.6 parts of PPG, 28.3 parts of DMPA (2,2-dimethylolpropanoic acid), 105.7 parts of IPDI, and 200 parts of NPAC were charged while introducing nitrogen gas, and the mixture was reacted at 90°C for 5 hours to obtain a urethane prepolymer solution having an isocyanate group at its end. Next, a mixture of 16.7 parts of AEA and 350 parts of IPA was added dropwise at room temperature over 60 minutes, and then the mixture was reacted at 70° C. for 3 hours to obtain a polyurethane resin solution. NPAC was added to the resulting polyurethane resin solution to adjust the solid content, thereby obtaining a solution of polyurethane resin P2 having a solid content concentration of 30%, a weight average molecular weight of 30,000, Mw / Mn=3.0 and an acid value of 39.3 mgKOH / g.
[0129] [Synthesis Example 1-3] (Polyurethane Resin P3) In a reactor equipped with a reflux condenser, a dropping funnel, a gas inlet tube, a stirrer, and a thermometer, 108.6 parts of PPA, 40.7 parts of PEG (a polyether polyol composed of polyethylene glycol and having a number average molecular weight of 2,000), 28.3 parts of DMPA, 105.7 parts of IPDI, and 200 parts of NPAC were charged while introducing nitrogen gas, and the mixture was reacted at 90°C for 5 hours to obtain a prepolymer solution having an isocyanate group at its end. Next, a mixture of 16.7 parts of AEA and 150 parts of IPA was added dropwise at room temperature over a period of 60 minutes, and then 10.0 parts of 28% ammonia water and 690 parts of ion-exchanged water were gradually added to neutralize the carboxyl groups in the resin and thereby make it water-soluble. Next, NPAC and IPA were distilled off under reduced pressure to obtain an aqueous solution of polyurethane resin P3 having a solid concentration of 30%, a weight average molecular weight of 32,000, Mw / Mn=3.3, and an acid value of 39.3 mgKOH / g. Note that the acid value of P3 is the value before neutralization.
[0130] [Synthesis Example 1-4] (Acrylic Resin P4) In a reactor equipped with a reflux condenser, a dropping funnel, a gas inlet tube, a stirrer, and a thermometer, 70 parts of styrene, 23 parts of acrylic acid, 7 parts of 2-hydroxyethyl methacrylate, 40 parts of EA (ethyl acetate), and 40 parts of IPA were charged while introducing nitrogen gas, and the temperature was raised to 90°C. 1 part of AIBN (azobisisobutyronitrile) and 15 parts of EA were added and a polymerization reaction was carried out for 4 hours, and further 0.1 part of AIBN and 3 parts of EA were added and reacted for 2 hours to obtain an acrylic resin solution. EA was added to the obtained acrylic resin solution to adjust the solid content, thereby obtaining a solution of acrylic resin P4 having a solid content concentration of 30%, a weight average molecular weight of 27,000, an acid value of 179.1 mgKOH / g, and a hydroxyl value of 30.2 mgKOH / g.
[0131] [Synthesis Example 1-5] (Water-based acrylic resin P5) In a reactor equipped with a reflux condenser, a dropping funnel, a gas inlet tube, a stirrer, and a thermometer, 40 parts of ion-exchanged water and 0.2 parts of Adeka Reasoap SR-10 (manufactured by ADEKA Corporation) as a surfactant were charged while introducing nitrogen gas, and 1% of a pre-emulsion in which 42 parts of styrene, 8 parts of acrylic acid, 10 parts of 2-hydroxyethyl methacrylate, 40 parts of 2-ethylhexyl acrylate, 1.8 parts of SR-10, and 53 parts of ion-exchanged water were mixed in advance was further added. After the internal temperature was raised to 70°C and sufficient nitrogen replacement was performed, 10% of 10 parts of a 5% aqueous solution of potassium persulfate was added to initiate polymerization. After the reaction system was kept at 70°C for 5 minutes, the remaining pre-emulsion and the remaining 5% aqueous solution of potassium persulfate were dropped over 3 hours while maintaining the internal temperature at 70°C, and stirring was continued for another 2 hours. Thereafter, the temperature was cooled to 30° C., and the pH was adjusted to 8.5 with 18% aqueous ammonia to obtain an aqueous acrylic resin emulsion. The solid content was adjusted by adding ion-exchanged water to the obtained aqueous acrylic resin emulsion to obtain an aqueous acrylic resin emulsion P5 having a solid content concentration of 30%, a mass average molecular weight of 35,000, an acid value of 62 mgKOH / g, and a hydroxyl value of 43 mgKOH / g. Note that the acid value in P5 is the value before neutralization.
[0132] [Synthesis Example 1-6] (Polyester P6) 302.5 parts of terephthalic acid, 302.5 parts of isophthalic acid, 135.6 parts of ethylene glycol, and 227.3 parts of neopentyl glycol were charged into a reactor, and the mixture was gradually heated to 160-240 ° C. while stirring under a nitrogen stream to carry out an esterification reaction. After reacting at 240 ° C. for 1 hour or more and the acid value became 15 or less, the reactor was gradually depressurized to 1-2 torr, and after reaching a predetermined viscosity, the reactor was cooled to 200 ° C., 32.1 parts of trimellitic anhydride were charged, and the mixture was reacted at 200 ° C. for 2 hours to carry out terminal acid modification. EA was added to the obtained polyester resin to adjust the solid content, and a polyester resin solution P6 with a solid content concentration of 30%, a weight average molecular weight of 10,000, and an acid value of 22.4 mg KOH / g was obtained.
[0133] <Production of primer layer-forming composition (primer composition)> [Production Example 1-1] (Primer composition S1) 84 parts of polyurethane resin P2 solution, 3 parts of isocyanate curing agent A (Asahi Kasei Duranate P301-75E), 5 parts of EA, 5 parts of IPA, and 3 parts of silica particles (Mizusawa Chemicals P-73: hydrophilic silica particles with an average particle size of 3.8 μm) were stirred and mixed using a disper to obtain primer composition S1.
[0134] [Production Examples 1-2 to 15, Comparative Production Examples 1-1 and 1-2] (Primer Compositions S2 to S15, SS1, and SS2) Except for changing the raw materials and compounding ratios shown in Table 1, primer compositions S2 to S15, SS1, and SS2 were obtained in the same manner as in Production Example 1-1.
[0135] [Table 1]
[0136] The abbreviations in Table 1 are shown below. Maleated rosin: A solution of Arakawa Chemical's Malkied No. 32 (acid value 130 mg KOH / g, solids concentration 100%) diluted with ethyl acetate to a solids concentration of 30%. Isocyanate-based hardener A: Duranate P301-75E (manufactured by Asahi Kasei) Isocyanate-based hardener B: Duranate D-101 (manufactured by Asahi Kasei) Isocyanate-based hardener C: Takenate D-110NB (Mitsui Chemicals) Isocyanate-based hardener D: Coronate AQ-130 (manufactured by Young Sun Chemtrade) Carbodiimide curing agent A: Carbodilite V-05 (Nisshinbo Chemical) Carbodiimide curing agent B: Carbodilite E-02 (Nisshinbo Chemical) EA: Ethyl acetate IPA: Isopropyl alcohol
[0137] <Production of polyols used in adhesives> [Synthesis Example 2-1] (Polyester polyol B1) In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tank and a nitrogen gas inlet tube, 124 parts of ethylene glycol, 212 parts of neopentyl glycol, 368 parts of 1,6-hexanediol, 645 parts of isophthalic acid, 36 parts of adipic acid and 265 parts of sebacic acid were charged, and the mixture was heated to 250°C while stirring under a nitrogen stream to carry out an esterification reaction. After a predetermined amount of water was distilled and the reaction was continued until the acid value was 5 or less, the pressure was gradually reduced and a deglycolization reaction was carried out at 1 mmHg or less for 5 hours to obtain a polyester polyol. Then, 35 parts of isophorone diisocyanate was gradually added, and the reaction was carried out at 150°C for about 2 hours to obtain a polyester polyurethane polyol. 12.0 parts of ethylene glycol bis-anhydrotrimellitate were added to 100 parts of this polyester polyurethane polyol and reacted at 180°C for approximately 2 hours. The mixture was then diluted with ethyl acetate until the solids concentration reached 50%, yielding a solution of partially acid-modified polyester polyol B1 with a number average molecular weight of 9,000 and an acid value of 30.3 mgKOH / g.
[0138] [Synthesis Example 2-2] (Polyester polyol B2) A reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tank and a nitrogen gas inlet tube was charged with 58 parts of ethylene glycol, 412 parts of diethylene glycol, 343 parts of neopentyl glycol, 517 parts of isophthalic acid and 393 parts of adipic acid, and the mixture was heated to 250 ° C. while stirring under a nitrogen stream to carry out an esterification reaction. After a predetermined amount of water was distilled and the reaction was continued until the acid value was 5 or less, the pressure was gradually reduced and a deglycolization reaction was carried out at 1 mmHg or less for 5 hours to obtain a polyester polyol. 4.0 parts of trimellitic anhydride were added to 100 parts of this polyester polyol, and the mixture was reacted at 180 ° C. for about 2 hours, and then diluted with ethyl acetate until the solid content concentration was 50%, to obtain a solution of partially acid-modified polyester polyol B2 with a number average molecular weight of 2,000 and an acid value of 23.5 mgKOH / g.
[0139] <Preparation of polyisocyanate solution> [Preparation Example 1] (Polyisocyanate C1) Coronate 2785 (biuret type polyisocyanate derived from hexamethylene diisocyanate, manufactured by Tosoh Corporation) was diluted with ethyl acetate to adjust the solid concentration to 50% and NCO% to 9.6%, to obtain a solution of polyisocyanate C1.
[0140] <Adhesive manufacturing> [Manufacturing Example 2-1] (Adhesive D1) 90 parts of polyester polyol B1 solution, 10 parts of polyester polyol B2 solution, and 8 parts of polyisocyanate C1 solution were mixed, and ethyl acetate was added to prepare adhesive solution D1 with a solids concentration of 30%.
[0141] <Manufacture of deinking treatment liquid (deinking liquid)> [Production Example 3] (Treatment Solution A1) 0.1 parts of polyoxyethylene stearyl ether (POE addition number: 12, HLB: 13.9) as a surfactant, 0.01 parts of BYK-1650 (manufactured by BYK Japan, silicone-based emulsion type defoamer, solids concentration 27.5%) as an antifoaming agent, 2 parts of sodium hydroxide, and 96.9 parts of water were mixed and stirred with a disperser to obtain treatment liquid A1.
[0142] <Manufacturing of laminates, separation and recovery of laminates (deinking test)> The manufacturing method of the laminate is described below. In the case of oil-based primer composition and printing ink, they were diluted with a mixed solvent of EA / IPA (mass ratio 70 / 30) to a viscosity of 15 seconds (25°C, Zahn cup #3 (manufactured by Rigo Co., Ltd.) before use. In the case of water-based, they were diluted with a mixed solvent of water / IPA (50 / 50) to a viscosity of 15 seconds before use. The thickness of the primer layer and the printing layer were each adjusted to about 1.5 μm.
[0143] [Example 1] (Laminate L1) The diluted primer composition S1 was printed on OPP (corona-treated stretched polypropylene film, thickness 20 μm) using a gravure printing machine equipped with a gravure plate with a plate depth of 30 μm, and dried at 50 ° C. to obtain a laminate having a structure of a base layer (OPP) / primer layer (S1). After aging at 25 ° C. for 24 hours, the primer layer printed surface was measured by FT-IR, and it was confirmed that the remaining rate of the peak derived from the curing agent was 0%. Next, on the primer layer of the obtained laminate, diluted printing ink R1W (Toyo Ink general-purpose lamination ink "LP Bio SX R631 White") and diluted printing ink R1C (Toyo Ink general-purpose lamination ink "LP Bio SX R39 Indigo") were printed using a gravure printing machine equipped with a gravure plate with a plate depth of 30 μm, and dried at 50 ° C. to obtain a laminate L1 having a structure of a base layer (OPP) / primer layer (S1) / printing layer (R1). The image quality of the laminate was evaluated as follows. Next, 500 g of the treatment liquid A1 and 10 g of a sample cut into a size of 1 cm x 1 cm from the laminate L1 obtained above were placed in a 1000 mL stainless steel beaker and stirred under conditions of 70 ° C. and 2500 rpm. The separation and recovery state of the laminate was evaluated as follows.
[0144] [Examples 2 to 14, 16 to 24, Comparative Examples 1 to 9] (Laminates L2 to 14, L16 to 24, LL1 to 9) Laminates L2 to 14, L16 to 24, and LL1 to 9 were obtained in the same manner as in Example 1, except that the substrate, primer composition, printing ink, and aging conditions after printing of the primer layer were changed to those shown in Table 2. Thereafter, in the same manner as in Example 1, the image quality of the laminate and the state of separation and recovery of the laminate were evaluated. The results are shown in Table 2.
[0145] [Example 15] (Laminate L15) The diluted primer composition S1 was printed onto OPP using a gravure printing machine equipped with a gravure plate with a plate depth of 30 μm, and dried at 50° C. to obtain a laminate having a substrate layer (OPP) / primer layer (S1) configuration. After aging at 25° C. for 24 hours, the printed surface of the primer layer was measured by FT-IR, and it was confirmed that the remaining rate of the peak derived from the curing agent was 0%. Next, diluted printing ink R1C (Toyo Ink's general-purpose laminating oil-based ink "LP Bio SX R39 Indigo") and diluted printing ink R1W (Toyo Ink's general-purpose laminating ink "LP Bio SX R631 White") were printed on the primer layer of the obtained laminate using a gravure printing machine equipped with a gravure plate with a plate depth of 30 μm, and dried at 50°C to obtain a laminate having a configuration of base layer (OPP) / primer layer (S1) / printing layer (R1). Next, adhesive D1 was applied to the printed layer of the obtained laminate using a dry laminator in an amount of 2 g / m2 after drying. 2 After coating and drying so that the coating was uniform, it was laminated with a CPP (unstretched polypropylene film, thickness 50 μm) to obtain a laminate L15 having a structure of base layer (OPP) / primer layer (S1) / printed layer (R1) / adhesive layer (D1) / base layer (CPP). Thereafter, in the same manner as in Example 1, the image quality of the laminate and the state of separation and recovery of the laminate were evaluated.
[0146] [Example 25] (Laminate L25) A laminate L25 was obtained in the same manner as in Example 15, except that the primer composition was changed to the content shown in Table 2. Thereafter, in the same manner as in Example 1, the image quality of the laminate and the state of separation and recovery of the laminate were evaluated. The results are shown in Table 2.
[0147] The abbreviations in Table 2 are as follows: OPP: Corona-treated oriented polypropylene film, thickness 20μm CPP: Non-oriented polypropylene film, thickness 50μm PET: Polyethylene terephthalate film, thickness 12μm R1W: Toyo Ink's general-purpose oil-based laminating ink "LP Bio SX R631 White" R1C: Toyo Ink Co., Ltd. general-purpose laminating oil-based ink "LP Bio SX R39 Indigo" R2W: Toyo Ink Co., Ltd. general-purpose oil-based ink for surface printing "PANNECO AM 630 White Y" R2C: Toyo Ink Co., Ltd. general-purpose oil-based ink for surface printing "PANNECO AM 39 Indigo" R3W: Toyo Ink's general-purpose water-based lamination ink "JW303 Aquaecol R63S White" R3C: Toyo Ink's general-purpose water-based laminating ink "JW303 Aquaecol R39 Indigo"
[0148] <Image quality evaluation of laminate> (concentration) The reflection density value at the 100% gradation point was measured using an X-Rite530. Based on the measured values, the image quality was evaluated according to the following criteria: A, B, and C are in the range where there is no problem in practical use. A (Excellent): Reflection density value is 2.1 or higher. B (Good): The reflection density value is 1.7 or more and less than 2.1. C (unacceptable): The reflection density value is less than 1.7.
[0149] (trapping) The reflection density value at the 50% gradation point was measured using a Spectro Plate from Techkon Co., Ltd. Based on the measured values, the image quality was evaluated according to the following criteria: A, B, and C are in the range where there is no problem in practical use. A (Excellent): The dot area ratio is 50% or more. B (Good): The dot area ratio is 40% or more and less than 50%. C (unacceptable): The dot area ratio is less than 40%.
[0150] (Adhesion to substrate) Cellophane tape (12 mm wide) manufactured by Nichiban Co., Ltd. was applied onto the printed layer of the laminate, and the tape was slowly peeled off, and then suddenly peeled off halfway through, and the degree of peeling of the ink coating was evaluated. In addition, for Examples 15 and 25, the evaluation was performed using the printed matter before being laminated with an adhesive. A (Excellent): The ink film does not peel off at all even when peeled off suddenly. B (Good): The ink film partially peels off where it is peeled off quickly, but the ink film does not peel off where it is peeled off slowly. C (Not acceptable): The ink coating peels off in the area that is peeled off slowly.
[0151] (Releasability) Thirty minutes after the start of stirring, the substrate was sampled, washed with water and dried. The removal rate of the printed layer of the obtained substrate was visually confirmed and evaluated according to the following criteria. A (Excellent): 100% of the printed layer peels off. B (Good): 90% or more of the printed layer peels off. C (Fail): 90% or more of the printed layer does not peel off.
[0152] (Reattachability) One hour after the start of stirring, the detached substrate was collected in a sieve with 1 mm openings, washed with water, and dried. Ten substrates were sampled, and the ten substrates were stacked and measured for color value L using a spectrophotometer (X-rite eXact, manufactured by X-rite). * x , a * x , b * x was measured. Similarly, for the substrate before printing, cut the substrate (20 g) to a size of 1 cm x 1 cm, immerse it in the release solution A1 (500 g), stir it at 70 °C and 2500 rpm for 1 hour, rinse it with water, dry it, and then sample 10 sheets. Stack the 10 substrates and measure the color value L * y , a * y , b * y was measured. The color difference ΔE was calculated using the following formula, and the re-adhesion was evaluated according to the following criteria. (Formula)ΔE=((L * x -L * y )2 +(a * x -a * y ) 2 +(b * x -b * y ) 2 ) 1 / 2 A (Excellent): ΔE is less than 2 B (Good): ΔE is 2 or more and less than 7 C (unacceptable): ΔE is 7 or more
[0153] (Manufacturing of recycled film and evaluation of transmittance) One hour after the start of stirring, the detached substrate was recovered, washed with water, and dried. The recovered substrate was then extruded at 200°C using a single-screw extruder and pelletized to obtain pellets of recycled resin. The recycled resin was then extruded at 200°C using a T-die film molding machine to produce a recycled film with a thickness of 30 μm. Regarding the coloration of the recycled film, the total light transmittance was measured using a haze meter (SH7000, manufactured by Nippon Denshi Kogyo Co., Ltd.) and evaluated according to the following criteria. A (Excellent): Total light transmittance is 90% or more B (Good): Total light transmittance is 70% or more but less than 90% C (unacceptable): Total light transmittance is less than 70%
[0154] [Table 2]
[0155] The above evaluation results show that the method according to the embodiment of the present invention not only provides excellent image quality for the printed layer, but also enables the plastic substrate to be easily detached from the laminate, resulting in a high-quality recycled substrate with little reattachment of the printed layer, etc., and further provides a high-quality molding material with little discoloration.
Claims
1. A method for producing a laminate having at least a plastic substrate, a primer layer containing a structural unit derived from a curing agent, and a printed layer in this order, comprising the steps of: A primer layer forming step of providing the primer layer on the plastic substrate; an aging step of aging the primer layer after the primer layer forming step such that a remaining rate of a peak derived from a curing agent measured by a Fourier transform infrared spectrophotometer (FT-IR) is 20% or less; A printing layer forming step of providing the printing layer on the primer layer after the aging step, The method for producing a laminate, wherein the primer layer is a layer that can be removed in a removing liquid in order to recover the plastic substrate.
2. The method for producing a laminate according to claim 1 , wherein the curing agent is a polyisocyanate compound.
3. The method for producing a laminate according to claim 1 , wherein the curing agent is a carbodiimide compound.
4. 4. The method for producing a laminate according to claim 1, wherein the primer layer contains a compound that dissolves or swells in an alkaline aqueous solution.
5. The method for producing a laminate according to claim 4 , wherein the compound that dissolves or swells in an alkaline aqueous solution has an acidic group.
6. The method for producing a laminate according to any one of claims 1 to 3, wherein the plastic substrate is a polyolefin substrate.
7. The method for producing the laminate according to any one of claims 1 to 3, which is used for producing a packaging material.
8. A method for separating and recovering plastic substrates, comprising contacting a laminate obtained by the method for producing a laminate according to any one of claims 1 to 3 with a release liquid to release and recover the plastic substrates.
9. A method for producing a molding material, comprising melt-kneading the plastic substrate recovered by the method for separating and recovering plastic substrates according to claim 8.
10. A method for producing a molded body, comprising hot molding a molding material obtained by the method for producing a molding material according to claim 9.
Citation Information
Patent Citations
Laminate adhesive having detachability from composite film, laminate, and method for recycling sheet-like substrate
JP2020196808A
Packaging material, packaging container, and method for producing recycling base material
JP2021088408A
Package, and manufacturing method of recycling substrate
JP2021091476A
Packaging materials, recycled molding materials and their manufacturing methods
JP2023036517A
Laminate having primer composition layer for desorption
JP2023081285A